Bacteria from fish and other aquatic animals [ a practical identification manual - Buller, Nicky B. (CABI, 2004)
"This manual provides a resource for the identification of bacteria that may be found in animals (particularly fish) that inhabit the aquatic environment. The emphasis is on bacteria from farmed aquatic animals and the contents include interpretation ofbiochemical identification tests and sets, biochemical identification tables, technical methods, and techniques for the molecular identification of bacteria. It will be useful to researchers in veterinary science and animal health as well as aquaculture and microbiology."--Jacket.